The The Relationship of Discomfort in Pregnancy with Physical Activity of Third Trimester Pregnant Women - Anggraeni, Sri; Srinayanti, Yanti; Litasari, Resna (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2024)
Women during pregnancy experience many changes in themselves, both physically and psychologically. Changes continue to occur during the 9 months of pregnancy, physical and psychological discomfort has been felt from the beginning of pregnancy. Then, coupled with the majority of pregnant women entering the third trimester of pregnancy, experiencing comfort disturbances that have an impact on the fulfillment of daily activities. During the third trimester, the abdomen is getting bigger, causing it to be unable to move freely, and the ability to move is decreasing, so that pregnant women tend not to be able to carry out daily activities optimally because of limited movement. Objective: This study aims to determine the relationship between discomfort in pregnancy and physical activity of pregnant women in the third trimester. Research method: quantitative analytic survey with cross sectional research design. The population in this study was 23 third trimester pregnant women in Banjaranyar Village. Sampling in this study used a total sampling of 23 respondents. Results: show that the age of the majority of respondents is reproductive age (20-35 years) 56.5%. Most of the respondents have low education, as many as 16 respondents with a total of 69.6%. The parity frequency of the majority of respondents was primiparous, i.e. had given birth to as many as 10 respondents with a total of 43.5%. From 23 respondents, the frequency of pregnant women feeling discomfort was 21 respondents (91.3%), pregnant women doing light activities were 18 respondents (78.3%). Conclusion: There is a relationship between discomfort in pregnancy and physical activity of pregnant women in Banjaranyar Village, Banjaranyar District with P Value 0.001 = 0.05.